Fibrillar collagen clamps lung mesenchymal cells in a nonproliferative and noncontractile phenotype - Schuliga, Michael J; See, Ian; Ong, Siau Chi; Soon, Lilian; Camoretti-Mercado, Blanca; Harris, Trudi; Stewart, Alastair G (American journal of respiratory cell and molecular biology, 2009)
Pulmonary fibrosis is characterized by phenotypic changes to mesenchymal cells and an increase in the deposition of fibrillar collagen (fCollagen). This study investigated the effect of type I fCollagen on the phenotypic plasticity of human parenchymal fibroblasts (PFbs) in vitro. Cell numbers were 45% lower when cultured on fCollagen as compared with culture on its degradation product, monomeric collagen (mCollagen). DNA profiles indicated that fCollagen is antiproliferative, rather than proapoptotic. fCollagen suppressed basic fibroblast growth factor-stimulated increases in the levels of cyclin E and CDK2 mRNA. fCollagen also suppressed transforming growth factor-beta (100 pM)-stimulated increases in the mRNA and protein levels of alpha-smooth muscle actin (alpha-SMA), a marker of the myofibroblast phenotype. However, in cells exposed to fCollagen, the levels of matrix metalloproteinase (MMP)-1 and -14 mRNA, as well as active MMP-2 protein, were increased by between two- and fivefold. The MMP inhibitors, ilomastat (10 microM) and doxycycline (30 microM), attenuated the dissolution of collagen fibrils by fibroblasts maintained on fCollagen, with a corresponding decrease in cell number. Ilomastat also reduced alpha-SMA expression and the capacity of PFb to contract three-dimensional fCollagen gels. Thus, exposure of fibroblasts to the fibrillar form of type I collagen in vitro reduces cell proliferation, increases MMP production and activation, and attenuates differentiation of PFb into myofibroblasts. fCollagen appears to apply a phenotypic clamp on lung fibroblasts that may be partially released by autocrine MMP activity.